Ordinary (p1, …, pm)-Laplacian systems with mixed boundary value conditions. (April 2016) - Averna, Diego; Tornatore, Elisabetta
Abstract: In this paper we prove the existence of multiple weak solutions for an ordinary mixed boundary value system with ( p 1, …, p m )-Laplacian by using recent results of critical points.